Hoek–Brown rock mass: adjusting Geological Strength Index for directional strength - Baczynski, NRP (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Rock mass shear strength is often directional due to sets of geological defects that co-align with failure paths. In the limit, the entire path may be defined by co-aligned defects and rock mass strength in that direction is equal to defect strength plus the strength of any intact rock bridges that may exist between such defects. Conceptual considerations (Baczynski 2018) and a large number of case studies (Baczynski 2019a, b) indicate strong linear relationships between relative occurrences (%) of co-aligned defects and intact rock bridges and the adjustments required in the Geological Strength Index (GSI) input to Hoek–Brown equations to quantify the directional shear strength. GSI adjustment is a two-step process. The general rock mass GSI is first negatively adjusted for relative portion (%) of failure path length that is defined by geological defects coaligned with the path. GSI is then positively adjusted for relative portion (%) of failure path length defined by intact rock bridges between the co-aligned defects. GSI (directional) is computed as GSI (general rock mass) minus GSI (defect adjustment) plus GSI (bridge adjustment). For general design, GSI (defect adjustment) is 0.4 × (occurrence (%) of co-aligned defects) and GSI (bridge adjustment) is 1.2 × (occurrence (%) of intact rock bridges along the failure path). Correlation coefficients for the proposed adjustments are typically 0.75 to 0.95. GSI adjustment factors may be further refined by mi and rock type. The geotechnical data that needs to be collected to enable GSI adjustment is discussed. Indicative step-path case study results used to develop the recommended GSI adjustments are shown. Example data for probabilities (%) of occurrence for defects and intact rock bridges and their respective lengths are tabulated. Use of the Rosenblueth method to develop statistical models is explained.
Keywords: Hoek–Brown rock mass; directional strength; data collection; case studies; GSI adjustment